Nutrition and metabolism theory and practices - Capidlac, Rose Jean D. (Arcler Press, 2017)
Metabolism is the chemical process of transforming food into fuel. Metabolism is closely linked to nutrition and the availability of nutrients. Food provides a variety of substances that are essential for the building, upkeep, and repair of body tissues, and for the efficient functioning of the body. This book provides thorough coverage of the processes involved in metabolism and nutrition.